Analisis Watak Pada Novel Lupus Karya Hilman Hariwijaya - Omar Alfariq; Emran Hasanain (Yayasan Gema Bina Nusantara, 2023)
The novel is inseparable from literary criticism, which tends to evaluate literary works interreby dismantling, dismantling, as thoroughly as possible, as deep as possible and the lationships in the elements of literary works. Some things that need to be considered in the novel are intrinsic and extrinsic elements. The study of intrinsic elements uses an objective approach by analyzing the structure, namely the theme, mandate, point of view, setting, plot, style of language, and characters/characterizations. This analysis is to find out the structure of the story in Muhammad Afrilianto's Novel Meraih Bintang.